Microsatellite markers from the ‘South American fruit fly’ Anastrepha fraterculusa: valuable tool for population genetic analysis and SIT applications - Lanzavecchia, Silvia Beatriz; Juri, Marianela Lucía; Bonomi, Angelica; Gomulski, Ludvik; Scannapieco, Alejandra Carla; Segura, Diego Fernando; Malacrida, Anna; Cladera, Jorge Luis; Gasperi, Giuliano (BioMed Central, 2018)
Background: Anastrepha fraterculus Wiedemann is a horticultural pest which causes significant economic losses in the fruit-producing areas of the American continent and limits the access of products to international markets. The use of environmentally friendly control strategies against this pest is constrained due to the limited knowledge of its population structure. Results: We developed microsatellite markers for A. fraterculus from four genomic libraries, which were enriched in CA, CAA, GA and CAT microsatellite motifs. Fifty microsatellite regions were evaluated and 14 loci were selected for population genetics studies. Genotypes of 122 individuals sampled from four A. fraterculus populations were analyzed. The level of polymorphism ranged from three to 13 alleles per locus and the mean expected heterozygosity ranged from 0.60 to 0.64. Comparison between allelic and genotypic frequencies showed significant differences among all pairs of populations. Conclusions: This novel set of microsatellite markers provides valuable information for the description of genetic variability and population structure of wild populations and laboratory strains of A. fraterculus. This information will be used to identify and characterize candidate strains suitable to implement effective pest control strategies and might represent a first step towards having a more comprehensive knowledge about the genetics of this pest.